2010
DOI: 10.1016/j.freeradbiomed.2010.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Early and late administration of MnTE-2-PyP5+ in mitigation and treatment of radiation-induced lung damage

Abstract: Introduction Chronic production of reactive oxygen and nitrogen species is an underlying mechanism of radiation (IR)-induced lung injury. The purpose of this study was to determine the optimum time of an antioxidant and redox-modulating Mn porphyrin, MnTE-2-PyP5+, delivery to mitigate and/or treat IR-induced lung damage. Methods Female Fischer-344 rats were irradiated to their right hemithorax (28 Gy). Irradiated animals were treated with PBS or MnTE-2-PyP5+ (6 mg/kg/24h) delivered for 2 weeks by s.c.- impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 84 publications
4
98
1
Order By: Relevance
“…Both drugs are similarly potent SOD mimics with respect to k cat , yet MnTnHex-2-PyP 5þ was effective in vivo at a 120-fold lower dose (123,32). Importantly, protection was observed even when the administration started as late as 8 weeks (and lasted 2 weeks) after the lung irradiation (124). The decrease in the breathing-rate frequencies and tissue damage, and suppression of oxidative stress and signaling pathways, involving activated macrophages, HIF-1a, VEGF, and TGF-b were detected.…”
Section: Parkinson's Diseasementioning
confidence: 97%
“…Both drugs are similarly potent SOD mimics with respect to k cat , yet MnTnHex-2-PyP 5þ was effective in vivo at a 120-fold lower dose (123,32). Importantly, protection was observed even when the administration started as late as 8 weeks (and lasted 2 weeks) after the lung irradiation (124). The decrease in the breathing-rate frequencies and tissue damage, and suppression of oxidative stress and signaling pathways, involving activated macrophages, HIF-1a, VEGF, and TGF-b were detected.…”
Section: Parkinson's Diseasementioning
confidence: 97%
“…Further exploration indicated that at least one major transcription factor, NF-jB, has been inactivated by the action of MnP (240). Similarly, the radioprotective effect of MnP was demonstrated when it was given for the duration of two weeks starting at any time postradiation from 2 h up to 8 weeks (96). HIF-1a and the genes it controls (VEGF, TGF-b) have been involved (95,96).…”
mentioning
confidence: 98%
“…Similarly, the radioprotective effect of MnP was demonstrated when it was given for the duration of two weeks starting at any time postradiation from 2 h up to 8 weeks (96). HIF-1a and the genes it controls (VEGF, TGF-b) have been involved (95,96). In cancer studies, the impact of MnP on activator protein-1 (AP-1) has been shown (304).…”
mentioning
confidence: 99%
“…In the laboratory, a wide range of late normal tissue injuries can be mitigated using therapies that are not started until days to weeks after irradiation 25,[46][47][48][49][50][51][52][53][54] . Such mitigation was first demonstrated in models of renal injury using angiotensin-converting enzyme inhibitors (ACEis) that are commonly used in human beings to treat hypertension and heart disease 46 .…”
Section: Progress On Mitigation Of Late Normal Tissue Injurymentioning
confidence: 99%
“…A second class of agents that has shown promise for mitigation of late radiation injuries are the superoxide and catalase mimetics 25,[52][53][54] . Unfortunately, the superoxide/ catalase mimetics that show promise as radiation mitigators in laboratory studies are not yet approved for human use.…”
Section: What If An Incident Happened Now?mentioning
confidence: 99%